Activation of biliverdin-IXα reductase by inorganic phosphate and related anions - MANTLE, TIMOTHY; FRANKLIN, EDWARD; DUNNE, AISLING; HAYES, JERRARD (My University, 2007)
The effect of pH on the initial-rate kinetic behaviour of BVR-A (biliverdin-IX? reductase) exhibits an alkaline optimum with NADPH as cofactor, but a neutral optimum with NADH as cofactor. This has been described as dual cofactor and dual pH dependent behaviour; however, no mechanism has been described to explain this phenomenon. We present evidence that the apparent peak of activity observed at neutral pH with phosphate buffer and NADH as cofactor is an anion-dependent activation, where inorganic phosphate apparently mimics the role played by the 2?-phosphate of NADPH in stabilizing the interaction between NADH and the enzyme. The enzymes from mouse, rat and human all exhibit this behaviour. This behaviour is not seen with BVR-A from Xenopus tropicalis or the ancient cyanobacterial enzyme from Synechocystis PCC 6803, which, in addition to being refractory to activation by inorganic phosphate, are also differentiated by an acid pH optimum with both nicotinamide nucleotides.
PUBLISHED
Keywords: anion activation; biliverdin-IX? reductase (BVR-A); Neuroscience